Synthesis of New Gemcitabine Derivatives Linked Tetrazole Ring as Antibacterial Activity - Fattah Naser, Ali; Kareem Madlool, Ammar; Hussein Mohsin, Dheyaa; Kareem Obaid, Ehab; Jabbar Radhi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
A series of novel tetrazole derivatives containing nucleoside analogs were synthesized by reaction between azido gemcitabine and nitrile compounds in the presence of ammonium chloride as a catalyst. The structures of all prepared compounds were analyzed by NMR and FTIR spectroscopic methods. The antibacterial activity of tetrazole derivatives was determined by using Streptococcus pneumoniae, Escherichia coli, and Staphylococcus aureus.